E-Service Quality dan E-Promotion Terhadap Keputusan Pembelian Konsumen pada Website Traveloka.com - Aditia Sovia Pramudita; Rahayu Eka Agustia (Politeknik Pos Indonesia, 2020)
E-Commerce has a very high growth rate which the needs of quickly and precisely are the main target in the e-commerce business. This study aims to determine how consumers respond to the implementation of e-service quality website, e-promotion website which leads into consumer purchasing decisions at Traveloka using a descriptive quantitative design with data collection techniques through a questionnaire. The method used in this research is descriptive analysis and multiple linear regression analysis. The results show that the effect of website e-service quality and website e-promotion on service purchasing decisions at Traveloka is positive and significant. The influence of e-service quality website and e-promotion website on purchasing decisions at Traveloka is 23%. While the rest is influenced by variables not included in this study.